The effects of cinnamaldehyde and eugenol on human adipose-derived mesenchymal stem cells viability, growth and differentiation: a cheminformatics and in vitro study - Abdorrahim Absalan; Seyed Alireza Mesbah-Namin; Taki Tiraihi; Taher Taheri (Mashhad University of Medical Sciences, 2016)
Objective: The aim of this study was to estimate the cheminformatics and qualitative structure-activity relationship (QSAR) of cinnamaldehyde and eugenol. The effects of cinnamaldehyde and eugenol on the viability, doubling time and adipogenic or osteogenic differentiations of human adipose-derived mesenchymal stem cells (hASCs) were also investigated.  Materials and Methods: QSAR and toxicity indices of cinnamaldehyde and eugenol were evaluated using cheminformatics tools including Toxtree and Toxicity Estimation Software Tool (T.E.S.T) and molinspiration server. Besides, their effects on the hASCs viability, doubling time and differentiation to adipogenic or osteogenic lineages were evaluated. Results: Cinnamaldehyde is predicted to be more lipophilic and less toxic than eugenol. Both phytochemicals may be developmental toxicants. They probably undergo hydroxylation and epoxidation reactions by cytochrome-P450. The 2.5 µM/ml cinnamaldehyde and 0.1 µg/ml eugenol did not influence hASCs viability following 72 hr of treatment. But higher concentrations of these phytochemicals insignificantly increased hASCs doubling time till 96 hr, except 1 µg/ml eugenol for which the increase was significant. Only low concentrations of both phytochemicals were tested for their effects on the hASCs differentiation. The 2.5 µM/ml cinnamaldehyde and 0.1 µg/ml eugenol enhanced the osteogenesis and decreased the adipogenesis of hASCs meaningfully. Conclusion: According to the cheminformatics analysis and in vitro study, cinnamaldehyde and eugenol are biocompatible and low toxic for hASCs. Both phytochemicals may be suitable for regenerative medicine and tissue engineering when used at low concentrations, but maybe useful for neoplastic growth inhibition when used at high concentrations.